Photovoltaics for educational television in rural schools - Cowan, William Douglas (Energy Research Centre, 2016)
One application for photovoltaic (PV) technology is in providing electricity for educational aids, in developing areas remote from grid supply. Technical, social and economic aspects of this option are investigated, in local context, by examining the use of small PV systems to power educational television and video in secondary schools in Bophuthatswana. Technical performance was assessed through monitoring PV system behaviour and climatic variables over an extended period, using remote data-capture techniques at a demonstration site. Modelling provided for further prediction of performance in nonobserved conditions. Social and educational aspects of the schools television project were investigated through interviews with educationists, planners, project administrators and a limited sample of teachers and pupils in Bophuthatswana. Overall conclusions are that PV systems can provide a reliable and technically appropriate solution to the problem of powering light electrical loads in off-grid schools. Levelised unit energy costs can be acceptable if PV systems are critically sized, and if there is close match between designed capacity and actual load energy demand. If this is not the case - as in Bophuthatswana school systems - unit energy costs may be very high. Organisational features of project implementation and inadequate central resources, particularly for delivering appropriate educational software to schools, have impaired the potential of the project, and the equipment in schools is under-utilised. Proceeding from an inductive performance analysis of the monitored system, a PV system performance model was developed, in order to assess the optimum sizing of components in small stand-alone photovoltaic systems in such applications, and to judge the sizing of the systems installed. The model is based upon critical runs of adverse weather, leading to-wards system loss of power to load. It predicts the minimum insolation required to avoid system loss of power to load over runs of days, and compares this with percentiles for plane-of-array insolation over runs of days, derived from long term · hourly weather station records. The approach allows development of a loss of power probability (LOPP) sizing methodology which preserves the run-length characteristics of local climatic data. Sizing predictions from this method are compared with other sizing methodologies, and are used to indicate design savings possible for the monitored systems. The proposed critical-run LOPP sizing method has potential for incorporation in a microcomputer-based sizing tool, suitable for more accurate design of photovoltaic systems with battery storage in local applications.